2022
DOI: 10.1177/00031348221084967
|View full text |Cite
|
Sign up to set email alerts
|

Unmasking the Confounder: The Inherent Physiologic Variability of Swine During an Automated Experimental Model of Ischemia-Reperfusion Injury

Abstract: Background We sought to determine the magnitude of the inherent inter-animal physiologic variability by automating a porcine Resuscitative Endovascular Balloon Occlusion of the Aorta (REBOA) protocol to minimize external influences that might alter physiology and confound experimental results. Methods Swine (n = 42) underwent a controlled 30% blood volume hemorrhage followed by 30 minutes of REBOA (ie, ischemic phase). The animals were weaned from REBOA autonomously over 15 minutes, beginning the reperfusion p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Furthermore, sample sizes should be determined a priori based on robust power calculations. However, we found consistency in cardiac function measurements at baseline and end of hemorrhage across groups, which demonstrates the rigor of instrumentation and automated experimental methodology to enable a reproducible hemorrhagic shock model ( 28 ). While there was decreased variability for most parameters after the controlled hemorrhage in all groups, there were some notable exceptions such as HR.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Furthermore, sample sizes should be determined a priori based on robust power calculations. However, we found consistency in cardiac function measurements at baseline and end of hemorrhage across groups, which demonstrates the rigor of instrumentation and automated experimental methodology to enable a reproducible hemorrhagic shock model ( 28 ). While there was decreased variability for most parameters after the controlled hemorrhage in all groups, there were some notable exceptions such as HR.…”
Section: Discussionmentioning
confidence: 62%
“…The elevated HR variability was not expected in a state of shock as others, such as Batchinsky et al and Carrara et al ( 29 , 30 ), have shown that acute stress from hemorrhagic shock can impair the autonomic nervous system and its modulation of heart rate. The consistency in cardiac function measurements at baseline and end of hemorrhage also demonstrates the rigor of the instrumentation and automated experimental methodology to enable a reproducible hemorrhagic shock model ( 28 , 30 , 31 ). Collectively, the results from this suggest that an n = 6 pigs/group is only adequately powered to detect a twofold increase in cardiac performance metrics (e.g., SV, CO).…”
Section: Discussionmentioning
confidence: 84%
“…Interindividual variability in response to surgical setup may have contributed to some of our findings. Our group has already highlighted the unexpected variability in response to a similar model 74 . Regardless, blood pressure alone is not a good marker of microperfusion overall.…”
Section: Discussionmentioning
confidence: 91%
“…Our group has previously investigated the inherent physiologic variability in an automated ischemia-reperfusion swine model and found significant differences in cardiovascular and biological response. Although this confounder seems to be unavoidable in preclinical in vivo models, it may offer a translational advantage as it effectively models clinical practice (41).…”
Section: Discussionmentioning
confidence: 99%